2006
DOI: 10.1115/1.2424973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Variational Modeling of Ionic Polymer Transducers

Abstract: Ionomeric polymers are a promising class of intelligent material which exhibit electromechanical coupling similar to that of piezoelectric bimorphs. Ionomeric polymers are much more compliant than piezoelectric ceramics or polymers and have been shown to produce actuation strain on the order of 2% at operating voltages between 1V and 3V (Akle et al., 2004, Proceedings IMECE). Their high compliance is advantageous in low force sensing configurations because ionic polymers have a very little impact on the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The magnitude of the ionic polymer model is tuned through the ratio of the coupling coefficient to the frequency-dependent permittivity, d/ T . For modeling purposes the permittivity was specified as 2 Â 10 À4 F/m at 75 Hz based upon published experimental results (Buechler and Leo, 2007). With this value for T , the IPT coupling coefficient d is estimated to be 4.4 Â 10 À13 (C/m 2 )/(N/m 2 ) to properly predict the magnitude of the experimental IPT response.…”
Section: Maximum Voltagementioning
confidence: 99%
“…The magnitude of the ionic polymer model is tuned through the ratio of the coupling coefficient to the frequency-dependent permittivity, d/ T . For modeling purposes the permittivity was specified as 2 Â 10 À4 F/m at 75 Hz based upon published experimental results (Buechler and Leo, 2007). With this value for T , the IPT coupling coefficient d is estimated to be 4.4 Â 10 À13 (C/m 2 )/(N/m 2 ) to properly predict the magnitude of the experimental IPT response.…”
Section: Maximum Voltagementioning
confidence: 99%
“…These methods were previously demonstrated using this material by the authors and were shown to be very effective. 7 The material properties are summarized in Figure 2.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…This model was extensively validated as a means of predicting both mechanical response to an electrical input and electrical response to a mechanical input. 7 In the sections that follow, we will develop a model of a square plate which can be modeled in two dimensions, briefly discuss the characterization of the materials, and then present an extensive model validation study.…”
Section: Introductionmentioning
confidence: 99%
“…In general, most IPT sensing experiments to date have imposed dynamic stimulation to study several parameters that are known to affect the sensor output in bending (i.e. counter-ion type, hydration level, diluent type, temperature and electrode material) over a range of the frequency bands (Newbury and Leo, 2003; Bennett and Leo, 2004; Bonomo et al, 2006; Buechler and Leo, 2007; Bonomo et al, 2008; Bahramzadeh and Shahinpoor, 2011) while some have looked at imposing impulse functions, ramps and periodic waves (Bonomo et al, 2006; Bahramzadeh and Shahinpoor, 2011). In contrast, relatively few reports focused on step displacement excitation in IPT parameters determination and sensing characterization.…”
Section: Introductionmentioning
confidence: 99%